Propionic Acid and Sodium Benzoate Affected Biogenic Amine Formation, Microbial Community, and Quality of Oat Silage - Jia, Tingting; Yun, Ying; Yu, Zhu (Frontiers in Microbiology, 2021)
Investigating the microbial communities and biogenic amine (BA) formation in silage is of vital for improving the quality and safety of oat silage. The present study evaluated the effects of propionic acid (P) and sodium benzoate (SB) on the quality properties, microbial communities, and biogenic amine (BA) formation in oat silage. Oat was harvested at boot stage and ensiled using P and SB as additives in mini silos, followed by 14 days of aerobic exposure. The results showed that P and SB improved fermentation quality of oat silage, increased the lactic acid content, decreased pH value and ammonia nitrogen content. Putrescine, cadaverine and tyramine were the dominant BAs in oat silage, spermidine and spermine were not detected. The control silage had the highest content of total biogenic amine (TBA, 2506.7 mg kg-1 DM), and decreased by 51.1% and 57.7% after adding P and SB, respectively. Moreover, a lower putrescine, cadaverine, and tyramine content and undesirable microbes, such as Caproiciproducens, Stenotrophomonas, Herbinix and Enterobacter genera, were observed in P and SB silages, which was beneficial for oat silage quality. The fungal community of P silage was dominated by Monascus fuliginosus, and the temperature, pH and ammonia nitrogen content increased after exposure to air. Sedimentibacter, Herbinix, Caproiciproducens, Enterobacter and Escherichia-Shigella were found to be positively correlated with BA formation in oat silage. Overall, P and SB effectively inhibit the undesirable microbes and BA formation in oat silage, the P silage exhibited lower aerobic stability than the SB silage.